Numerical analysis of a dental implant system in three-dimension - (:unkn) unknown (ELSEVIER SCI LTD, 2002)
One of the important problems in dental implant systems is screw loosening. In order to prevent this loosening a preload is applied to the retaining screw. However, this measure has not been able to eliminate its occurrence. In this study the effect of a washer in a Branemark-type implant on the loosening conditions of the retaining screw was investigated using a finite element simulation in three-dimensional models. The simulation indicated that a washer has an important affect against loosening. This also increases the flexibility of implant system against the deformation. The application of a washer is easy and cheap. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: three-dimensional contact modeling; implant system